Current Status, Challenges, and Possible Solutions of EEG-Based Brain-Computer Interface: A Comprehensive Review - Rashid, Mamunur; Sulaiman, Norizam; P. P. Abdul Majeed, Anwar; Musa, Rabiu Muazu; Ab. Nasir, Ahmad Fakhri; Bari, Bifta Sama; Khatun, Sabira (Frontiers in Neurorobotics, 2020)
Brain-Computer Interface (BCI), in essence, aims at controlling different assistive devices through the utilization of brain waves. It is worth noting that the application of BCI is not only limited to medical applications, and hence, the research in this field has gained due attention. Moreover, the significant number of publications over the past two decades, further indicates the consistent improvements, as well as breakthroughs that have been made in this particular field. Nonetheless, it is also worth mentioning that with these improvements, new challenges are constantly discovered. This article provides a comprehensive review of the state-of-the-art of a complete BCI system. First, a brief overview of electroencephalogram (EEG) based BCI system is been deliberated. Secondly, a considerable number of popular BCI applications are reviewed in terms of its electrophysiological control signals, feature extraction, classification algorithms as well as the performance evaluation metrics. Finally, the challenges to the recent BCI system are discussed, and the possible solutions to mitigate the issues are recommended.